THE INFLUENCE OF JOB SATISFACTION AND WORK MOTIVATION TOWARD EMPLOYEE PERFORMNCE IN PT INDOMARCO PRISMATAMA PONTIANAK - Anggraini, Masithah B1024141016 (Jurnal Manajemen Update, 2019)
AbstractThe purpose of this study was to determine the description of job satisfaction, work motivation and employee performance in PT Indomarco Prismatama Pontianak and analyse how much the influence of job satisfaction and work motivation toward employee performance. The sample in this research was 120 employees from PT Indomarco Prismatama Pontianak. The measurement of this study is using a Likert scale and analysed using SPSS 22. The tests which have been done are validity, reliability, classic assumption test, R square test and T test in order to analyse the relationship of all variables. Based on the research result, it can be known that job satisfaction and work motivation had positive and significant relationship on employee performance with coefficient of determination as much as 84 percent, while the other 16 percent is influenced by other variables which were not been analyzed in this research.Keywords: Job Satisfaction, Work Motivation, and Employee Performance. REFERENCES  Al-Aluf, Wild & Pudj Musmed (2017). Assessing The Impact Of Motivation, Job Satisfaction, And Work Environment On Employee Performance in Helthcare Service. International Journal of Scientific & Technology Research Volume 6, Issuse 10.Amirullah., & Budiyono, H. (2004). Pengantar Manajemen. Yogyakarta: Graha Ilmu.Anggriawan, D.A. (2012). Hubungan antara Leader-Member Exchange dan Kepuasan Kerja pada Karyawan bagian Operasional PT. Krakatau Steel (Persero) Tbk. (Unpublished Thesis), Universitas Indonesia.Anna, Salanova & Sanni, K (2010). Employee Satisfaction and Work Motivation. Mikeli University of Applied  Sciences.AR, A. A. (2012). Effect of Perceived Values On The Brand Preference and The Purchase Intention. European Scientific Journal, August edition vol 8, No. 17, 1-17.As'ad, M. (2004). Psikologi Industri. Yogyakarta: Liberty.Ferdiansyah, C. H. (2015).Handoko. (2000). Manajemen Sumber Daya Manusia. BPFE Yogyakarta.Harninda. (1999). Manajemen Sumber Daya Manusia. Retrieved from Jurnal Manajemen Sumber Daya Manusia: jurnal-sdm.blogspot.co.idFerdinand, A. (2002). Structural Equation Modelling dalam Penelitian Manajemen. Semarang: FE UNDIP.Ghozali, I. (2005). Aplikasi Analisis Multivariate dengan SPSS. Semarang: UNDIP.Hasibuan, M. S. (2003). Jakarta: PT Bumi Aksara.Heffner, C. L. (2016). Chapter 7.3 Test Validity and Reliability. Retrieved May 18, 2016, from Allphsych: http://allpsych.com/researchmethods/validityreliability/Hofstede, G. (1980). Culture and organizations. International Studies of Management and Organizations. Vol.10, 15-41.Katz, D., & Kahn, R. L. (1978). The social psychology of organizations. New York: Wiley.Kreitner, R., & Kinicki, A. (2009). Organizational Behavior: Key Concepts, Skill & Best Practices (4th ed.). New York: Mc Graw - Hill.Kreitner, R., & Kinicki, A. (2014). Organizational behaviour eighth edition. New York: McGraw-HillKusumawardana, Erza (2017).Langton, N., Robbins, S. P., & Robbins, S. P. (2007). Organizational behaviour: Concepts, controversies, applications. Toronto: Pearson Prentice Hall.Luthans, F. (2008). Organizational Behavior.  New York: McGraw-Hill.Mangkunegara, A. P. (2013). Manajemen Sumber Daya Perusahaan. Bandung: Remaja Rosdakarya.Mangkunegara. (2001). Manajemen Sumber Daya Manusia. Bandung: Remaja Rosdakarya.Melani, T., & Suhaji. (2012). Faktor-faktor yang Mempengaruhi Kepuasan Kerja (Studi pada Karyawan Sekolah Tinggi Ilmu Farmasi "Yayasan Pharmasi" Semarang. Jurnal Kajian Akuntansi dan Bisnis , 1 (1).Mora, M. (2011, February 21). Validity and Reliability in Surveys. Retrieved from Relevant Insights: Grow Your Business Based on Facts: http://www.relevantinsights.com/validity-and-reliabilityMusrinah. (2012). Faktor-Faktor Yang Mempengaruhi Kepuasan Kerja Pegawai Negeri Sipil Kantor Pusat Administrasi Universitas Syiah Kuala. Jurnal Ilmu Manajemen , 34-48.Nazir, M. (1988). Metode Penelitian. Jakarta: Ghalia Indonesia.Nhat, Nguyen & Dung Nguyen Van (2013). Effects of Motivation and Job satisfaction on Employees’ Performance at Petrovietnam Nghe an Construction Joints Stock Corporation (PVNC). International Journal of Business and Social Science Vol. 4 No. 6; June 2013. Nugroho, K. S. (2013). Pengaruh Pemberian Tunjangan Terhadap Kepuasan Kerja Karyawan. Jurnal Manajemen Sumber Daya Manusia .Noor, J. (2011). Metode Penelitian. Jakarta: Prenada Media Group.Northouse, P.G. (2013). Kepemimpinan: Teori dan Praktik (edisi keenam). Jakarta: PT. Indeks.Nurkholis. (2003). Manajemen Berbasis Sekolah : Teori, Model dan Apikasinya. Jakarta : Grasindo.Panggabean. S, & Mutiara (2004). Manajemen Sumber Daya Manusia. Bogor: Ghalia Indonesia.Periantalo, J., & Mansoer, W.D. (2008). Faktor-faktor yang Mempengaruhi Kesiapan Untuk Berubah Pegawai Di Dirjen PQR. JPS vol. 14, no. 03.Porter, L. W., Steers, R. M., Mowday, R.T., & Boulian, P.V. (1974). Organizational commitment, job satisfaction, and turnover among psychiatric technicians. Journal of Applied Psychology, 59(5), 603-609.Pribadi, J. A., & Harjanti, D. (2014). Pengaruh Penilaian Prestasi Kerja terhadap Motivasi Kerja Karyawan dengan Kompensasi Sebagai Variabel Intervening. AGRORA , 2 No 1.Ranupandjojo, H., & Suad, H. (2002). Manajemen Personalia. Yogyakarta: BPFE.Rayadi. (2012). Faktor Sumber Daya Manusia yang Meningkatkan Kinerja Karyawan dan Perusahaan di Kalimantan Barat. Jurnal EKSOS, 114-119.Rindawati, S. (2012). Analisa pengaruh praktik kinerja organisasi dan SDM terhadap kelancaran pelaksanaan tugas anggota DPRD Kabupaten Bengkulu Tengah. Jurnal JENIUS, 101-112Rivai, V., & Sagala, E. J. (2013). Jakarta: Rajawali Press.Robbins, S. P., & Coutler, M. (2012). Management. New York: Pearson.Robbins, S. P., & Judge, T. A. (2006). Organizational Behaviour tenth edition. New Jersey: Prentice Hall.Smither, R.D. (1994). The Psychology of Work and Human Performance. New York: HarperCollins College Publishers, Inc.Silalahi, U. (2002). Pemahaman Praktis Azas-azas Manajemen. Bandung: Mandar Maju.Soekidjan. (2009). Manajemen Sumber Daya Manusia. Jakarta: Bumi Aksara.Sofyandi. (2008). Manajemen Sumber Daya Manusia. Yogyakarta: Graha Ilmu.Spector, P.E. (2008). Industrial and Organizational Psychology: Research and Practice (fifth edition). USA: John Wiley & Sons, Inc.Sugiyono. (2013). Metode Penelitian Administrasi. Bandung: Alfabeta.Sugiyono. (2013). Metode Penelitian Kuantitatif, Kualitatif dan R&D. Bandung: Alfabeta.Sugiyono. (2014). Metode Penelitian Bisnis. Bandung: ALVABETA.Sugiyono. (2009). Statistika Untuk Penelitian. Bandung: CV. Alfabeta.Suhaji, T. M. (2012). Faktor-Faktor Yang Mempengaruhi Kepuasan Kerja (Studi Kasus Karyawan Sekolah Tinggi Ilmu Farmasi 'Yayasan Farmasi Semarang". Jurnal Manajemen , 1-22.Sujianto, A., E. (2009). Aplikasi Statistik Dengan SPSS. Jakarta: Prestasi Pustaka.Sutrisno, E. (2011). Manajemen Sumber Daya Manusia. Jakarta: Kencana Prenada Media Group.Swasto, B. (2011). Manajemen Sumberdaya Manusia. Malang: Universitas Brawijaya Press.Telvisia, I., & Suyasa, P. (2008). Kesesuaian Minat terhadap Pekerjaan: Pegawai Produktif (Studi pada Agen Asuransi Jiwa di Jakarta). Phonesis Jurnal Ilmiah Psikologi Industri dan Organisasi , 10, 76-95.Tosi, H. L., Rizzo, J. R., & Carroll, S. J. (1990). Managing organizational behaviour second edition. New York: Harper & Row.Umar, H. (2005). Metode Penelitian Untuk Skripsi dan Tesis Bisnis. Jakarta: PT. Raja Grafindo Persada.Usmany, T., A., Hamid, D., & Utami, N., H. (2016). Pengaruh Budaya Organisasi Terhadap Komitmen Organisasional Dan Kinerja Karyawan (Studi Pada Karyawan Pabrik Gondorukem Dan Terpentin Sukun Perum Perhutani Kesatuan Bisnis Mandiri Industri Gondorukem Dan Terpentin Ii, Ponorogo). Jurnal Administrasi Bisnis Vol.37, No.2.Wahyudi, B. (2002). Manajemen Sumber Daya Manusia. Bandung: Sulita.Wibowo, N.C., & Susanto, E.M. (2013). Pengaruh Kualitas Leader- Member Exchange (LMX) Terhadap Produktivitas Kerja Melalui Kepuasan Kerja dan Komitmen Organisasional Pada PT. Nutrifood Surabaya. AGORA vol. 1, no. 1.Wibowo. (2011). Manajemen Kinerja. Jakarta: PT. Raja Grafindo Persada.